Monoclonal Antibody As Anti Cancer Agents - Sahil, Kataria (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The recent clinical and commercial success of anticancer antibodies such as rituximab and trastuzumab has created great interest in antibody-based therapeutics for hematopoietic malignant neoplasms and solid tumors. In the recent years of immunologic research, we are witnessing development in the fields of antigen screening and protein engineering in order to create specific anticancer remedies. The developments in the field of recombinant DNA, protein engineering and cancer biology have let us gain insight into many cancer-related mechanisms. Moreover, novel techniques have facilitated tools allowing unique distinction between malignantly transformed cells, and regular ones. This understanding has paved the way for the rational design of a new age of pharmaceuticals: monoclonal antibodies and their fragments. Antibodies can select antigens on both a specific and a high-affinity account, and further implementation of these qualities is used to target cancer cells by specifically identifying exogenous antigens of cancer cell populations. The structure of the antibody provides plasticity resonating from its functional sites. This review will spot the light on some of the novel antibodies and antibody-based approaches that are being currently developed for the new generation of anticancer agents. Key words: Antibody, cancer immunotherapy, tumor antigens, anti tumor mechanisms, targeted therapy, antibody fusions.